The effects of different schedules of bortezomib, melphalan, and prednisone for patients with newly diagnosed multiple myeloma who are transplant ineligible: a matching-adjusted indirect comparison. Issue 3 (23rd February 2020) - Mateos, Maria-Victoria; San-Miguel, Jesus; Goldschmidt, Hartmut; Sonneveld, Pieter; Dimopoulos, Meletios A.; Heeg, Bart; Hashim, Mahmoud; Deraedt, William; Hu, Peter; Lam, Annette; He, Jianming
Abstract: For patients with newly diagnosed multiple myeloma (NDMM) who are transplant ineligible, bortezomib-melphalan-prednisone (VMP) demonstrated superior efficacy based on the VISTA trial. In subsequent trials, twice-weekly bortezomib was limited to the first cycle or completely replaced with once-weekly bortezomib to reduce toxicity. Following a systematic literature review, the efficacy and safety of modified VMP schedules (pooled data from the once-weekly bortezomib VMP arm of the GIMEMA trial and the VMP arm of the ALCYONE trial) were compared to the VISTA schedule using naïve and unanchored matching-adjusted indirect comparison (MAIC). Median progression-free survival was similar between VISTA and modified VMP (20.7 months [95% CI, 18.4–24.3] vs 19.6 months [95% CI, 18.8–21.0]). Peripheral neuropathy was significantly reduced with modified VMP versus VISTA VMP (all grades: naïve, 32.1% vs 46.8% and MAIC, 32.1% vs 46.7%; both p < .0001). These findings support a modified VMP dosing schedule for patients with NDMM who are transplant ineligible.